1995
DOI: 10.1007/bf00231944
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of grape (Vitis vinifera L.) zygotic-derived somatic embryos and regeneration of transgenic plants

Abstract: Transgenic grape plants were regenerated from somatic embryos derived from immature zygotic embryos of seedless grape (Vitis vinifera L.) selections. Somatic embryos were bombarded twice with 1 μm gold particles using the Biolistic PDS-1000/He device (Bio-Rad Laboratories) and then exposed to Agrobacterium tumefaciens strain C58/Z707 containing the binary plasmid pGA482GG or pCGN7314. Following cocultivation, secondary embryos were allowed to proliferate on Emershad/Ramming proliferation (ERP) medium for 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 16 publications
1
38
0
3
Order By: Relevance
“…These results are presumably due to both the toxic effects of PA and disturbance by PA oxidization, because previous reports showed that phenolic compounds and their oxidation cause the browning of plant tissue and physically disturb regeneration (Madhusudhanan and Rahiman, 2000;Tang and Newton, 2004;Johkan et al, 2008). The transformation of many fruit crops, such as apple, grapevine, kiwifruit, and persimmon, depends on adventitious bud regeneration from leaves or calluses in vitro (Maheswaran et al, 1992;Matsuta et al, 1993;Scorza et al, 1995;Tao et al, 1997;Koshita et al, 2008). However, our results suggested that it is difficult to regenerate transgenic plants with DkMyb4 via adventitious buds in vitro.…”
Section: Application Of Ectopic Dkmyb4 Expressionmentioning
confidence: 68%
“…These results are presumably due to both the toxic effects of PA and disturbance by PA oxidization, because previous reports showed that phenolic compounds and their oxidation cause the browning of plant tissue and physically disturb regeneration (Madhusudhanan and Rahiman, 2000;Tang and Newton, 2004;Johkan et al, 2008). The transformation of many fruit crops, such as apple, grapevine, kiwifruit, and persimmon, depends on adventitious bud regeneration from leaves or calluses in vitro (Maheswaran et al, 1992;Matsuta et al, 1993;Scorza et al, 1995;Tao et al, 1997;Koshita et al, 2008). However, our results suggested that it is difficult to regenerate transgenic plants with DkMyb4 via adventitious buds in vitro.…”
Section: Application Of Ectopic Dkmyb4 Expressionmentioning
confidence: 68%
“…The protocols used for transformation were modified from those described by Scorza et al (1995). Overnight cultures of Agrobacterium strain C58sZ707 or LBA4404 were grown in LB medium at 28 ° C in a shaking incubator.…”
Section: (43k)mentioning
confidence: 99%
“…~'From left to right: NPTII, Neomycin phosphotransferase II; 2enh, double cauliflower mosaic virus 35S enhancers; 35S or double 35S, CaMV 35S promoter; A1MV or CMV, alfalfa mosaic virus or cucumber mosaic virus -C 5' untranslated leader sequences, respectively; 35S or NOS, CaMV 35S or nopaline synthase terminators, respectively; GUS = 13-glucuronidase. al., 1995;Scorza et al, 1995Scorza et al, , 1996, although relatively few scion and rootstock genotypes were transformed and the regeneration rate has generally been low.…”
Section: Introductionmentioning
confidence: 99%
“…Um exemplo de transferência de grupos fosfato é o gene neo, que é amplamente usado como marcador de seleção na transformação de plantas (Fraley et al, 1983). O neo é responsável pela produção da enzima neomicina fosfotransferase II (NPTII (Scorza et al, 1995).…”
Section: Avaliação Da Eficiência De Transformaçãounclassified
“…Pode-se considerar que a presença de canamicina favorece a multiplicação de células transformadas na competição com células não transformadas, mesmo se permitir a regeneração de um grande número de falsos transformantes (Scorza et al, 1995). Em amendoim considerou-se que a inibição de crescimento pela canamicina era tão severa nos explantes inoculados com Agrobacterium como nos não inoculados, optando-se então pela não utilização do agente seletivo.…”
Section: Avaliação Da Eficiência De Transformaçãounclassified